2017
DOI: 10.1097/md.0000000000007077
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence trends in the characteristics of patients with allergic asthma in Beijing, 1994 to 2014

Abstract: This study aimed to determine the clinical profiles and prevalence trends during 1994 to 2014 among patients with allergic asthma (AA), which is a clinical phenotype of asthma.We retrospectively analyzed the characteristics of 319 patients who were diagnosed with AA between March 1, 1994 and February 28, 2014 at 3 Beijing centers.The patients included 155 males and 164 females, and the mean age was 50.86 ± 15.27 years (range 13–86 years). The proportions of asthma attacks in summer and autumn were 60.7% (1994–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…[18][19][20] But in this study, the results indicated that in this region male patients were more likely to be sensitive to allergens, and the sIgE positive rates of all individual allergens except cowry and mold mix were higher in males than females (Figure 1). This result was consistent with the findings in two previous studies.…”
Section: -13mentioning
confidence: 84%
See 1 more Smart Citation
“…[18][19][20] But in this study, the results indicated that in this region male patients were more likely to be sensitive to allergens, and the sIgE positive rates of all individual allergens except cowry and mold mix were higher in males than females (Figure 1). This result was consistent with the findings in two previous studies.…”
Section: -13mentioning
confidence: 84%
“…14,20,26 However, this is the first large-scale study to report the prevalence of allergen sensitization among patients with suspected allergic diseases in Henan Province, a central region of China. The finding in this study may also be applicable in other provinces in the central region of China which have similar climates, lifestyles to Henan, but further studies are needed to provide evidence.…”
Section: -13mentioning
confidence: 99%
“…Taken together, these data suggest importance differences in the underlying biology of asthma between males and females. Female sex has been identified as a risk factor for low health-related quality of life in asthma [100]. Females have a higher frequency of non-allergic asthma than males and have a higher frequency of healthcare contacts and hospitalisations indicating more severe asthma, which is also reflected in 2011 data from the Centers for Disease Control and Prevention showing a 30% increase in mortality from asthma in females compared to males [101].…”
Section: Asthmamentioning
confidence: 99%
“…However, these treatments are not effective for all patients (Tan et al, 2016). What’s worse, remarkable, reproducible and undesirable side effects of systemic corticosteroids can also be seen in treatment (Luo et al, 2017; Mao et al, 2017). Therefore, searching for a new antiasthmatic agent is a furious research field.…”
Section: Introductionmentioning
confidence: 99%